The Vegetation of Isoëto-Nano-Juncetea Class in the Sluch River Valley (Ukraine) - Korotka, Inna; Pashkevych, Nataliia (Biodiversity: Research and Conservation, 2017)
Vegetation of Isoëto-Nano-Juncetea class has been investigated in the Sluch River valley within the forest-steppe zone. We distinguished three associations belonging to Verbenion supinae (Pulicario vulgaris-Menthetum pulegii Slavnić 1951), Eleocharition ovatae (Cyperetum micheliani Horvatić 1931 and Veronico anagalloidis-Lythretum hyssopifoliae Wagner ex Holzner 1973) alliances. The floristic composition of these syntaxa, is rich in diagnostic species of Bidentetea tripartitae and Phragmito-Magnocaricetea classes, which could indicate a transition to more sustainable communities in the succession row. Our current work is a small portion of a large task to clarify the location of ‘hot spots’ across the overall diversity of Isoëto-Nano-Juncetea, and to identify where and how this diversity can be maintained best.